(untitled) (International journal of artificial intelligence, 2026)
This article scientifically and theoretically analyzes the psychological impact of classroom conflict dynamics on the formation of students’ motivation. During the study, the psychological essence of learning motivation, the factors causing classroom conflicts, and their influence on students’ emotional states and educational activities were examined. In addition, the influence of conflicts on students’ internal and external motivation, the importance of pedagogical communication, and the scientific foundations of creating a healthy psychological environment were analyzed. The article presents scientific conclusions and practical recommendations on developing students’ learning motivation through constructive conflict management.